Electric Current Generation by Increasing Sucrose in Papaya Waste in Microbial Fuel Cells - Rojas-Flores, Segundo (2022)
“The accelerated increase in energy consumption by human activity has generated an increase in the search for new energies that do not pollute the environment, due to this, microbial fuel cells are shown as a promising technology. The objective of this research was to observe the influence on the generation of bioelectricity of sucrose, with different percentages (0%, 5%, 10% and 20%), in papaya waste using microbial fuel cells (MFCs). It was possible to generate voltage and current peaks of 0.955 V and 5.079 mA for the cell with 20% sucrose, which operated at an optimal pH of 4.98 on day fifteen. In the same way, the internal resistance values of all the cells were influenced by the increase in sucrose, showing that the cell without sucrose was 0.1952 ± 0.00214 KΩ and with 20% it was 0.044306 ± 0.0014 KΩ. The maximum power density was 583.09 mW/cm2 at a current density of 407.13 A/cm2 and with a peak voltage of 910.94 mV, while phenolic compounds are the ones with the greatest presence in the FTIR (Fourier transform infrared spectroscopy) absorbance spectrum. We were able to molecularly identify the species Achromobacter xylosoxidans (99.32%), Acinetobacter bereziniae (99.93%) and Stenotrophomonas maltophilia (100%) present in the anode electrode of the MFCs. This research gives a novel use for sucrose to increase the energy values in a microbial fuel cell, improving the existing ones and generating a novel way of generating electricity that is friendly to the environment.“